Analisis Perubahan Luas Void Bekas Tambang Batubara Menggunakan Metode NDWI Di PT. Tebo Prima Kabupaten Tebo - Oktavia, Marisa; Rahmawati, Devit; desmawita, Desmawita; Marliantoni, Marliantoni; Muslim, Muslim (Innovative: Journal Of Social Science Research, 2025)
P.T Tebo Prima is a company engaged in coal mining which is located in the village of Sungai Bengkal Village. The mining method used is open pit mining using this method will cause an impact in the form of former mining holes which are commonly called voids. The aims of this research are to; Analyzing Existing Void Water Bodies Using the NDWI Method, and Analyzing Changes in Boundary Areas of Water Bodies. This study uses remote sensing-based data in the form of aerial photo data and Landsat 8 OLI/TIRS imagery. The method used in this study is the NDWI (Normalized Difference Water Index) method to compare the level of wetness in satellite images. This research uses Google Earth Pro, Global Mapper, and Surfer software. Based on the results of image data processing on the Global Mapper software, the area of ex-coal mining voids in May 2019 was 1.77 Ha, June was 1.33 Ha, July was 2.25 Ha, October was 2 ,77 Ha. Factors that  affect  changes  in the area of  water bodies  in the  voids are; Changes  in soil sedimentation in water bodies due to erosion by water There is water intrusion that enters through small rivers around the void, high rainfall in how many months so that it increases the water discharge in the void.   Keywords: Void; Change in Existing Void Area; NDWI